Insuficiencia renal crónica y su incidencia en la salud mental de una paciente de 50 años de la ciudad de Machala - Medina Siguenza, Emily Nahomi (2023)
This study is mainly based on the problem of a 50-year-old patient from the city of Machala who is diagnosed with Chronic renal failure, due to this catastrophic disease, her mental health was compromised in her depression, the patient has found herself very bad since she was diagnosed about 3 years ago, there are even times when she feels so discouraged that she stops attending her dialysis treatment at the hospital, which keeps her stable with her disease. In this case, they worked with cognitive behavioral therapy, in order to be able to modify their negative thoughts for more positive ones, reviewing the symptoms of each affected area, reaffirming the most appropriate technique for the problem they have. A psychometric test was applied, which is the Hamilton Depression Scale, with this applied test it helped me to control and verify the level of depression of the patient and the symptoms that he is presenting.